2021
DOI: 10.1186/s13019-021-01427-9
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex is associated with shorter hospital length of stay after open lobectomy for lung cancer: a retrospective observational study

Abstract: Background Sugammadex is associated with few postoperative complications. Postoperative pulmonary complications (PPC) are related to prolonged hospitalizations. Present study explored whether the use of sugammadex could reduce PPCs and thereby reduce hospital length of stay (LOS) after lung surgery. Methods We reviewed the medical records of patients who underwent elective open lobectomy for lung cancer from January 2010 to December 2015. Patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In addition, our study did not show a significant difference in the length of hospital stay between the two groups. In contrast, previous studies revealed that the administration of sugammadex reduced the length of hospital stay in major abdominal and thoracic surgeries [ 48 , 49 ]. We speculate that this may be because patients undergoing major surgery are at moderate to high risk of postoperative pulmonary complications [ 50 , 51 ], and sugammadex may reduce these risks [ 9 ].…”
Section: Discussionmentioning
confidence: 81%
“…In addition, our study did not show a significant difference in the length of hospital stay between the two groups. In contrast, previous studies revealed that the administration of sugammadex reduced the length of hospital stay in major abdominal and thoracic surgeries [ 48 , 49 ]. We speculate that this may be because patients undergoing major surgery are at moderate to high risk of postoperative pulmonary complications [ 50 , 51 ], and sugammadex may reduce these risks [ 9 ].…”
Section: Discussionmentioning
confidence: 81%
“…Postoperative pulmonary complication rate and average time from operation to discharge were reported to be significantly reduced in patients administered sugammadex than those administered pyridistigmine [ 43 , 44 ]. Ren M et al compared the cost-effectiveness of using sugammadex versus neostigmine in laparoscopic surgery and reported that sugammadex decreased the incidence of postoperative respiratory complications and related costs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathoracic surgery is associated with increased incidence of atelectasis and other PPCs because of the need for one-lung ventilation during surgery [ 5 ]. In a retrospective observational study of patients undergoing open lung lobectomy, the primary outcomes of hospitalization duration and postoperative atelectasis were significantly lower with sugammadex than with pyridostigmine [ 70 ]. Similarly, in a retrospective study of patients undergoing single-port video-assisted lung lobectomy, early postoperative abnormalities on chest radiography were significantly lesser with sugammadex than with pyridostigmine [ 71 ].…”
Section: Recent Researches In Specific Patient Populations or Surgeriesmentioning
confidence: 99%